Implementation of hardware and software of solar panel testing parameters - Saha, Joymit; Alam, Minhaz Morshed; Farha, Nusa; Mishi, Kazi Umme Jahan (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.